2007
DOI: 10.1002/jbm.b.30889
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of bonding strength between biomimetic apatite coating and substrate

Abstract: Bone-like apatite coatings were prepared using a biomimetic method in a modified simulated body fluid (m-SBF). The effect of the m-SBF volume on the apatite coating quality was studied. Three m-SBF volumes, 50, 100, and 200 mL, were employed to immerse titanium substrates in a sealed container so as to produce apatite coatings with different properties, namely types I, type II, and type III apatite coatings, respectively. The coatings were characterized using X-ray diffraction and environmental scanning electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 61 publications
(129 reference statements)
4
22
0
Order By: Relevance
“…20,34 Our previous study indicated that the higher the bicarbonate ion concentration in the SBF, the denser the coating that was formed. 35 This study further supported our finding. Table III shows that the apatite coating formed at 408C with a low initial pH was more porous than the coating formed in a solution with a high or medium initial pH due to different bicarbonate contents in the SBF during apatite formation.…”
Section: Discussionsupporting
confidence: 94%
“…20,34 Our previous study indicated that the higher the bicarbonate ion concentration in the SBF, the denser the coating that was formed. 35 This study further supported our finding. Table III shows that the apatite coating formed at 408C with a low initial pH was more porous than the coating formed in a solution with a high or medium initial pH due to different bicarbonate contents in the SBF during apatite formation.…”
Section: Discussionsupporting
confidence: 94%
“…Qu et al reported that they formed HA films on sandblasted, gritted and acid-etched titanium metal by aqueous solution method using SBF with modified ion composition [26]. They reported that bonding strength of the formed HA film was approximately 8–18 MPa.…”
Section: Resultsmentioning
confidence: 99%
“…46 Hence, the adhesion of apatite coatings is one of critical properties closely related to biocompatibility and longevity of metallic implants. 47 However, the modes of coating failure are quite complicated for pull-out tests, including adhesion failure, cohesive failure, and glue failure. By carefully controlling the volume of a modified SBF, Qu et al enhanced the tensile bonding strength of a biomimetic apatite coating up to 17.23 ± 2.55 MPa.…”
Section: Discussionmentioning
confidence: 99%